Aligning nuclear cluster orbits with an active galactic nucleus accretion disc. Issue 2 (5th October 2020) - Fabj, Gaia; Nasim, Syeda S; Caban, Freddy; Ford, K E Saavik; McKernan, Barry; Bellovary, Jillian M
ABSTRACT: Active galactic nuclei (AGN) are powered by the accretion of discs of gas on to supermassive black holes (SMBHs). Stars and stellar remnants orbiting the SMBH in the nuclear star cluster (NSC) will interact with the AGN disc. Orbiters plunging through the disc experience a drag force and, through repeated passage, can have their orbits captured by the disc. A population of embedded objects in AGN discs may be a significant source of binary black hole mergers, supernovae, tidal disruption events, and embedded gamma-ray bursts. For two representative AGN disc models, we use geometric drag and Bondi–Hoyle–Littleton drag to determine the time to capture for stars and stellar remnants. We assume a range of initial inclination angles and semimajor axes for circular Keplerian prograde orbiters. Capture time strongly depends on the density and aspect ratio of the chosen disc model, the relative velocity of the stellar object with respect to the disc, and the AGN lifetime. We expect that for an AGN disc density $ρ \gtrsim 10^{-11}{\rm g\, cm^{-3}}$ and disc lifetime ≥1 Myr, there is a significant population of embedded stellar objects, which can fuel mergers detectable in gravitational waves with LIGO-Virgo and LISA.